The Effect of Learning Intercultural Communicative Competence on English Foreign Language Learners’ Identity - SAADI, Samia (My University, 2018)
Intercultural communicative competence (ICC) is considered as a relevant aspect which links various cultural perspectives around the world. This study aims to investigate the effect of learning intercultural communicative competence on English foreign language (EFL) learners’ identity. To be more accurate and objective, this research study is devoted to confirming whether the ICC learning process affects the EFL learners’ identity, this latter was based on the development aspect of their identity in particular. We have used the mixed method. The use of the combination qualitative and quantitative methods in order to conduct our research hypothesis and cover the main ICC aspects. The work is divided into three chapters: the first tackles the historical backgrounds of ICC. The second deals with the methodology perceptions of the research and the results. The observation and questionnaires are the tools used for collecting data. The observation was a form of a checklist aims to shed the light on the developmental process of the learners’ concerning motivation, attitudes, cultural openness and their understanding of the the ICC savoirs. Concerning the students’ questionnaire aims to examine their understanding of the concept of ICC. Moreover, the teachers’ questionnaire , it aims to highlight their experience in teaching ICC. Furthermore, the research findings show that fostering intercultural communicative competence has a positive impact on EFL learners’ identity. Accordingly, students showed great interest and engagement towards it. this latter helps them to improve their various abilities towards the language learning process.
Case study: First year Master Students of Language and Communication at Abd Elhamid Ibn Badis University
Keywords: Intercultural Communicative Competence; Identity